Gas Phase Structure of Metal Mediated (Cytosine)2Ag+Mimics theHemiprotonated (Cytosine)2H+Dimer ini‑Motif Folding - Berdakin, Matias (2014)
The study of metal ion–DNA interaction aiming to understand the stabilization of artificial base pairing and a number of noncanonical motifs is of current interest, due to their potential exploitation in developing new technological devices and expanding the genetic code. A successful strategy has been the synthesis of metal-mediated base pairs, in which a coordinative bond to a central metal cation replaces a H-bond in a natural pair. In this work, we characterized, for the first time, the gas phase structure of the cytosine···Ag+···cytosine (C–Ag+–C) complex by means of InfraRed-MultiPhoton-Dissociation (IR-MPD) spectroscopy and theoretical calculation. The IR-spectrum was confidently assigned to one structure with the Ag+ acting as a bridge between the heteronitrogen atoms in each cytosine (both in the keto-amino form). This structure is biologically relevant since it mimics the structure of the hemiprotonated C–H+–C dimer responsible for the stabilization of the i-motif structure in DNA, with the replacement of the NH···N bond by a stronger N···Ag+···N bond. Moreover, since the structure of the C–Ag+–C complex is planar, it allows an optimum intercalation between pairs of the two antiparallel strand duplex in the DNA i-motif structure.